Status of Human Trafficking In South Wollo Zone, Amhara Regional State, Ethiopia: Implication for Counseling - Mezgebu Bayu Bezabih (Journal La Sociale, 2020)
The main purpose of this study was to examine situations of human trafficking with particular reference to South Wollo zone, Amhara regional state. Crosse sectional research design was applied and 40 Participants were took part in the study using availability sampling technique .This means those who were available at agar Ethiopia refugee’s camp during the time of data collection were inculcated into the study. The required data was collected through questionnaire and interview and then data was analyzed by using both quantitative methods such as one sample t-test and percentage as well as qualitative methods like thematic analysis. The finding of this study in on one sample t- test revealed that, the status of human trafficking, in the sample zone is high; there is increment of migration of Amhara dwellers from their native area to Areb countries. The root causes for the outbreak of human trafficking is linked with economic reason, be fool of brokers, inappropriate contestation among parents who live in the same geographical area. In line with the consequences of human trafficking, the trafficked have encountered different challenges such as exploitation of money for brokers, rape by brokers as well as paymasters as well their relatives and assassination too. Among these, rape is the most common one that the majority of trafficked are faced.